ESKEA: Enhanced Symmetric Key Encryption Algorithm Based Secure Data Storage in Cloud Networks with Data Deduplication - Elkana Ebinazer, Silambarasan; Savarimuthu, Nickolas; Mary Saira Bhanu, S. (Wireless personal communications, 2021)
Data deduplication approach is utilized in cloud storage to decrease the bandwidth of communication and storage space by eliminating the data copies from the cloud service provider (CSP). However, one of the main problems of cloud storage is data deduplication with secure data storage. To overcome this issue, the researchers presented symmetric data storage methods based on an encryption algorithm. Nonetheless, the Enhanced Symmetric Key Encryption Algorithm (ESKEA) based on secure data storage with data deduplication is proposed in this research to further improve data confidentiality. In this approach, the block-level deduplication of data is performed using the Convergent Encryption (CE) algorithm to check the CSP duplicate copies of data. Then, ESKEA algorithm is presented for secure storage of data. In ESKEA, Spider Monkey Optimization Algorithm (SMOA) optimally selects the secret key. The results of this work showed that the execution of the proposed ESKEA is more effective than that of the SKEA in terms of upload time and download time.